TRACING THE ANTIBACTERIAL, ANTIFUNGAL AND ANTI-BIOFILM ACTIVITIES OF ROOT EXTRACT BAJAKAH TAMPALA (SPATHOLOBUS LITTORALIS HASSK) - Setyowati, Endang; Irzani, Elza Fadia; Mochtar Luthfi, Chaerul Fadly; Hamzah, Hasyrul (Jurnal Farmasi Sains dan Praktis, 2024)
Biofilm is a common causative factor for urinary tract infections due to catheter usage with a percentage of infection around 70-80%. The Bajakah tampala (Spatholobus littoralis Hassk) is one of native plants of Kalimantan which contains phenolic compounds, flavonoids and tannins which are proven to accelerate wound healing, have antibacterial activity, and have very high and strong antioxidant activity. This study aims to determine the antibacterial and anti-biofilm activity of bajakah root extract (Spatholobus littoralis Hassk) on catheter colonies of Staphylococcus aureus, Escherichia coli and Candida albicans and to determine their mechanism of action in vitro. This research is carried out with an in vitro experimental study design using a microplate reader. Extraction was carried out by maceration method using 96% ethanol solvent. The results showed that the ethanol extract of Bajakah tampala (Spatholobus littoralis Hassk) had antibacterial activity against S. aureus with a concentration of 1% w/v of 88.33% ± 0.01 and anti-biofilm activity of 82.21% ± 0.01. E. Coli bacteria had an antibacterial activity of 84.83% and an anti-biofilm activity of 80.11 at a concentration of 1% w/v. C. albicans had an antifungal activity at a concentration of 1% w/v of 82.31% ± 0.01 and anti-biofilm activity of 77.00% ± 0.01. From these results it can be concluded that the ethanol extract of Bajakah tampala (Spatholobus littoralis Hassk) has antibacterial and antifungal activities and the potential as a new anti-biofilm agent against S.aureus, E. coli and C. albicans